Transformational Leadership and Achievement Motivation as Predictors of Teacher Performance - Pranata; Krisma Natalia; I Wayan Superbry (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Teacher performance is a crucial factor in determining the quality of learning, but problems remain, including suboptimal principal leadership and teacher achievement motivation, which impact performance achievement. This study aims to analyze the influence of transformational leadership and achievement motivation on teacher performance at a senior high school (SMAN). The study employed a quantitative approach with a correlational design. The study population consisted of 40 teachers, all of whom served as respondents. Data were collected through a questionnaire that had been tested for validity and reliability, then analyzed using descriptive statistics and multiple linear regression. The results showed that transformational leadership and achievement motivation had a positive and significant effect on teacher performance, both partially and simultaneously. Both variables contributed significantly to explaining variations in teacher performance. This finding indicates that improving teacher performance requires a synergy between effective transformational leadership and strengthening achievement motivation. The implications of this study emphasize the importance of developing principal leadership capacity and teacher motivation enhancement programs as strategies to improve the quality of learning and education.